HOMICIDAL DEATHS BY FIREARMS IN PESHAWAR: AN AUTOPSY STUDY - Hussain, Zahid; Shah, Mian Mujahid; Afridi, Hakim Khan; Arif, Muhammad (Journal of Ayub Medical College Abbottabad, 2006)
Background: Medico legal autopsies can be valuable sources of information about the distribution of causes of reported deaths, particularly in homicidal cases. The present study provides information regarding the homicidal deaths due to firearm injuries in the district of Peshawar, NWFP, Pakistan. Methodology: This descriptive study was conducted over the period of the year 2004. Data were collected from the autopsy records of the Department of Forensic Medicine, Khyber Medical College Peshawar and included all reported unnatural deaths from urban and rural areas of district Peshawar on whom autopsies were conducted in the department. Results: Homicidal deaths constituted 77.7% (492/633) of all autopsies for the year 2004. Of 492 homicidal deaths, a vast majority of 452 (91.87%) were caused by firearm injuries. Among these, the male to female ratio was 5.5:1. The most common firearm weapon (418/452, 92.5%) were high velocity rifled weapons (Kalashnikov, rifles, pistols), followed by low velocity rifled weapons (18/452, 3.98%) and shotguns (16/452, 3.54%). A total of 956 injuries were found in various body areas, giving an average of over two injuries per person. The head, face and neck sustained the highest injuries (257, 26.9%), followed by the chest (248, 25.9%) and abdomen (149, 15.6%); the extremities, buttocks and genitalia together sustained 302 (31.6%) injuries. Conclusion: The vast majority of reported homicides in Peshawar are caused by firearm injuries, which bring up issues related to possession of firearms and changes in cultural attitudes towards use of firearms, if a decrease in firearm-related homicides is desired. Key Words: Firearms, Homicide, Autopsy.